Imagined communities : constructing collective identities in medieval Europe - Pleszczyński, Andrzej; Sobiesiak, Joanna Aleksandra; Tomaszek, Michał, 1972-; Tyszka, Przemysław, 1969- (Explorations in medieval culture, 2018)
"Imagined Communities: Constructing Collective Identities in Medieval Europe offers a series of studies focusing on the problems of conceptualisation of social group identities, including national, royal, aristocratic, regional, urban, religious, and gendered communities. The geographical focus of the case studies presented in this volume range from Wales and Scotland, to Hungary and Ruthenia, while both narrative and other types of evidence, such as legal texts, are drawn upon. What emerges is how the characteristics and aspirations of communities are exemplified and legitimised through the presentation of the past and an imagined picture of present. By means of its multiple perspectives, this volume offers significant insight into the medieval dynamics of collective mentality and group consciousness"--